Quality Control Design on Customized Mica Packaging Craft Product - Agustine Eva Maria Soekesi; Veronica Kusdiartini; Bayu Prestyanto; Meniek Srining Prapti (Journal of Management and Business Environment (JMBE), 2021)
Quality is one of differentiation strategies that can be addressed to achieve competitive advantage. Many alternatives can be selected to achieve this purpose. One of them is to maintain good quality of the products. A craft souvenir enterprise in Semarang controls the operation system of every product it produces to meet a good quality. This is very important since it produces customized products in which each product is designed according to customer order. A case study was conducted on the mica packaging craft product. Observations for 3 months with weekly production period show that the proportion of defective products is still relatively high compared to that is set by the enterprise (3.6% against 3%). By using the Statistical Process Control method and follow-up using the fishbone diagram method, it is found that there are 3 main causes, namely material, man (labor), and machine factors. Refer to this analysis, corrective actions is carried out to reduce occurrence of defective products in the next production periods.